Respuesta :
Answer:
Step-by-step explanation:
2n - 6
a) n = 1 ; 2n - 6 = 2*1 - 6 = 2 - 6 = -4
n = 2 ; 2n - 6 = 2*2 - 6 = 4 - 6 = -2
n = 3 ; 2n - 6 = 2*3 - 6 = 6 - 6 = 0
b) n=10; 2n - 6 = 2*10 - 6 = 20 - 6 = 14
Answer:
Step-by-step explanation:
hello : let An = 2n - 6
1) the first three terms are :
the first term is : when n= 1 A1 =2(1)-6 = 2-6 = -4
the second term is : when n= 2 A2 = 2(2)-6 = 4-6 = -2
the third term is : when n= 3 A3 = 2(3)-6 = 6-6=0
2) the tenth term is : when n= 10 A10=2(10)-6 =20-6=14